2023
DOI: 10.1186/s13018-023-03778-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of the potential mechanism of Yi-Guan-Jian decoction to reverse bone loss in glucocorticoid-induced osteoporosis

Abstract: Background Glucocorticoid-induced osteoporosis (GIOP) is a disease in which long-term use of glucocorticoid causes bone loss, deterioration of bone microstructure and fracture. Currently, clinical drugs targeting this disease have certain side effects. There is still a need to find effective drugs with fewer side effects. The theory of traditional Chinese medicine suggests that YGJ has therapeutic effect on GIOP, but it has not been explained. Therefore, this study aims to explore the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Following many years of use, YGJ is now accepted as an effective therapy for liver fibrosis and CH. YGJ can regulate M1/M2 macrophage polarization and treat hepatic inflammation [ 7 ].YGJ also balances metabolic disorders, regulates metabolites, such as heptaphylloside, taurine, and uric acid, and exerts anti-inflammatory and antioxidant effects to alleviate systemic inflammatory responses [ 8 ]. Clinical studies revealed that YGJ not only alleviated clinical symptoms in patients with liver disease but also reduced serum alanine transaminase (ALT) and aspartate transaminase (AST) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Following many years of use, YGJ is now accepted as an effective therapy for liver fibrosis and CH. YGJ can regulate M1/M2 macrophage polarization and treat hepatic inflammation [ 7 ].YGJ also balances metabolic disorders, regulates metabolites, such as heptaphylloside, taurine, and uric acid, and exerts anti-inflammatory and antioxidant effects to alleviate systemic inflammatory responses [ 8 ]. Clinical studies revealed that YGJ not only alleviated clinical symptoms in patients with liver disease but also reduced serum alanine transaminase (ALT) and aspartate transaminase (AST) levels.…”
Section: Introductionmentioning
confidence: 99%